Language, Identity and Cycling in the New Media Age Exploring Interpersonal Semiotics in Multimodal Media and Online Texts - Kiernan, Patrick (Palgrave Macmillan UK, 2018)
This book examines how identities associated with cycling are evoked, narrated and negotiated in a media context dominated by digital environments. Arguing that the nature of identity is being impacted by the changing nature of the material and semiotic resources available for making meaning, the author introduces an approach to exploring such identity positioning through the interrelated frameworks of Systemic Functional Linguistics and Multimodal Analysis, and illustrates how this happens in practice. The book is divided into three parts, each of which focuses on a different aspect of identity and media environment. Part I considers celebrity identities in the conventional media of print and television. Part II investigates community and leisure / sporting identity through an online cycling forum, while Part III examines corporate identity realised through corporate websites, consumer reviews and Youtube channels. This unique volume will appeal to students and scholars of discourse analysis, applied linguistics and the world of cycling. Patrick Kiernan is Associate Professor in the School of Business Administration at Meiji University, Japan. His research specialises in Applied Linguistics and he is the author of Narrative, Identity and Language Teaching. He is also an avid cyclist. .